Gaps in EU foreign policy : the role of concepts in European studies - Larsen, Henrik (Palgrave Macmillan, 2020)
Contents: Gaps in EU Foreign Policy; Contents; List of Figures; 1 Introduction; Note; 2 The Performativity of Theories; 2.1 Performativity; 2.2 Derrida and Performativity; 2.3 Implications for the Study of the Performativity of the CEG; 2.4 Derrida's Double Reading; 2.5 Double Reading and the CEG; 3 The Capability-Expectations Gap: A Double Reading; 3.1 First Reading; 3.1.1 The Capability-Expectations Gap, or Conceptualising Europe's International Role; 3.1.2 Closing the Capabilities-Expectations Gap? (1998); 3.1.3 Hill's Subsequent Work on the CEG; 3.1.4 The Dominant CEG Narrative; 3.2 Second Reading. Contents: 3.2.1 Summary of Deconstructivist ReadingNotes; 4 The Performativity of the Capability-Expectations Gap; 4.1 The CEG as Standard Reference; 4.2 CEG as Framework for Analysis; 4.3 Transformation of the CEG Through Identification of Other Gaps; 4.4 Concluding Remarks; Notes; 5 Implications of the Gap Discourse for the Study of (European) Foreign Policy and European Studies; 5.1 European Foreign Policy; 5.2 Foreign Policy Analysis -- The State as an Ideal Type; 5.3 European Studies; References; Index.